2015
DOI: 10.1007/s11751-015-0218-2
|View full text |Cite
|
Sign up to set email alerts
|

Femoral supracondylar focal dome osteotomy with plate fixation for acute correction of frontal plane knee deformity

Abstract: Focal dome osteotomy (FDO) allows deformity correction without secondary translational deformity. The purpose of this study was to evaluate the degree of correction and knee functional outcome after correction of frontal knee deformity using femoral supracondylar FDO fixed with plate and screws. A prospective study included 12 consecutive cases of femoral frontal plane deformity that underwent correction using supracondylar focal osteotomy fixed by plate and screws. Average age was 27 years, while mean follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…Functional assessment using the Boston et al score also showed significant improvement, similar to the findings of Gupta et al and those of Agarwal and Shaharyar using the same score [14,17]. In radiological assessment, radiological tibiofemoral angle, MAD, and mLDFA all showed significant improvement, a finding that was in accordance with various other studies [14,16,18,19].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Functional assessment using the Boston et al score also showed significant improvement, similar to the findings of Gupta et al and those of Agarwal and Shaharyar using the same score [14,17]. In radiological assessment, radiological tibiofemoral angle, MAD, and mLDFA all showed significant improvement, a finding that was in accordance with various other studies [14,16,18,19].…”
Section: Discussionsupporting
confidence: 88%
“…This was due to a significant fall two months after the procedure, which led to plate and screw breakage. Plate and screw breakage was not seen in any other studies [14,15,18,19,[22][23][24]. In our case, this might have been due to the significant trauma and due to lack of contour between the plate and osteotomy site, which might have led to increased tension on the implant-bone construct, thereby making the implant prone to breakage.…”
Section: Discussionmentioning
confidence: 47%
“…Using a Center Of Rotation of Angulation (CORA) at the level of the knee joint is possible to perform a distal femoral focal dome osteotomy achieving deformity correction without leg length variations. Moreover, bone cuts are completely congruent with big contact surfaces allowing increased healing rate (32). Nevertheless, only few reports in literature described the outcomes of femoral dome osteotomies.…”
Section: Others Surgical Techniquesmentioning
confidence: 99%
“…Conservative therapy is not effective in managing this post‐traumatic deformity. To restore the function of joint maximally, surgical correction of the displaced mechanical axis is needed. Different distal femoral osteotomies have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Different distal femoral osteotomies have been proposed. However, the shortcomings of different osteotomies have remained obvious and there is no consensus about the most appropriate strategy. Medial open‐wedge distal femoral osteotomy (OW‐DFO) is an anatomically corrective procedure for varus deformity.…”
Section: Introductionmentioning
confidence: 99%